A region of consistent deletion in neuroblastoma maps within human chromosome 1p36.2-36.3. - White, P S (1995)
Deletion of the short arm of human chromosome 1 is the most common cytogenetic abnormality observed in neuroblastoma. To characterize the region of consistent deletion, we performed loss of heterozygosity (LOH) studies on 122 neuroblastoma tumor samples with 30 distal chromosome 1p polymorphisms. LOH was detected in 32 of the 122 tumors (26%). A single region of LOH, marked distally by D1Z2 and proximally by D1S228, was detected in all tumors demonstrating loss. Also, cells from a patient with a constitutional deletion of 1p36, and from a neuroblastoma cell line with a small 1p36 deletion, were analyzed by fluorescence in situ hybridization. Cells from both sources had interstitial deletions of 1p36.2-36.3 which overlapped the consensus region of LOH defined by the tumors. Interstitial deletion in the constitutional case was confirmed by allelic loss studies using the panel of polymorphic markers. Four proposed candidate genes--DAN, ID3 (heir-1), CDC2L1 (p58), and TNFR2--were shown to lie outside of the consensus region of allelic loss, as defined by the above deletions. These results more precisely define the location of a neuroblastoma suppressor gene within 1p36.2-36.3, eliminating 33 centimorgans of proximal 1p36 from consideration. Furthermore, a consensus region of loss, which excludes the four leading candidate genes, was found in all tumors with 1p36 LOH.